Anlotinib combined with radiotherapy and chemotherapy for recurrent pelvic osteosarcoma treatment: a case report and literature review - Qian Chen; Kai Zheng; Ming Xu; Ning Yan; Gong Hai; Xiuchun Yu (Frontiers in Oncology, 2023)
At present, the treatment of recurrent pelvic osteosarcoma is too simple, and most of the patients are treated with chemotherapy, radiotherapy, and/or combined surgery. Here, we report a 29-year-old man diagnosed with local recurrent pelvic osteosarcoma. Imaging showed that the tumor had obvious enhancement and abundant blood vessels. There was no indication of surgery. After the patient’s consent was obtained, we used anlotinib as a sequential treatment to chemotherapy. During the first course of adjuvant chemotherapy, we treated the patient with intensity-modulated radiotherapy (IMRT) with a total dose of 60 Gy equivalents. No disease recurrence was reported at 25 months after multimodal combination therapy.